DIDACTIC PROCESS OF PERCEPTION OF NATURE AND IMAGE - Furman, O.I. (Pedagogy of Higher and Secondary Education, 2022)
The paper considers the process of perceiving of a nature and image by the art students as well a the problem of didactical conditions and ways this process is subject of. We show that correct perceiving depends essentially o f a realization and studying by the students the scientific principles of a construction of image.